Estudio de la respueta de Anthonomus grandis al paration metilico en Nicaragua - Gonzalez M, D.F.=700 1 Laboucheix, J.
(En, Es)
Ilus., 12 ref.
Keywords: ANTHONOMUS GRANDIS; INSECTA; COLEOPTERA; CURCULIONIDAE; PLAGAS DE PLANTAS; GOáYPIUM; CONTROL DE PLAGAS; CONTROL QUIMICO; METIL PARATION; NICARAGUA; PICUDO DEL ALGODONERO; REVISTA NICARAGUENSE DE CIENCIAS AGROPECUARIAS